2005
DOI: 10.1002/cncr.20779
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐seated, well differentiated lipomatous tumors of the chest wall and extremities

Abstract: BACKGROUND Intramuscular lipomas and atypical lipomatous tumors (ALT) are common deep‐seated lipomatous tumors of the chest wall and extremities. Distinguishing between these two entities can be difficult based on histologic analysis alone. However, the cytogenetic profiles of ALT and intramuscular lipomas are distinct. Correct classification is important, because aggressive local disease recurrence occurs more frequently in patients with ALT than in patients with intramuscular lipoma. The authors examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 21 publications
(35 reference statements)
3
72
1
Order By: Relevance
“…However, it has also become apparent that these cytogenetic-histopathologic associations are not absolute. Hence, occasionally, and it should be emphasized that this applies also to tumors thoroughly analyzed by expert soft tissue pathologists, a lesion with typical morphology might display a chromosome rearrangement strongly associated with another diagnostic entity, e.g., a seemingly conventional lipoma without any signs of nuclear atypia, lipoblasts, or brown fat cell differentiation might still display a supernumerary ring chromosome, a breakpoint in 8q12 or a translocation affecting 11q13 Fletcher et al, 1996;Bassett et al, 2005;Brandal et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it has also become apparent that these cytogenetic-histopathologic associations are not absolute. Hence, occasionally, and it should be emphasized that this applies also to tumors thoroughly analyzed by expert soft tissue pathologists, a lesion with typical morphology might display a chromosome rearrangement strongly associated with another diagnostic entity, e.g., a seemingly conventional lipoma without any signs of nuclear atypia, lipoblasts, or brown fat cell differentiation might still display a supernumerary ring chromosome, a breakpoint in 8q12 or a translocation affecting 11q13 Fletcher et al, 1996;Bassett et al, 2005;Brandal et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…These data have shown that lipomas are characterized by a non-random pattern of karyotypic changes, which could be subdivided, in decreasing order of frequency, into four main categories: (1) structural rearrangements, in particular translocations, of chromosome bands 12q13-15, resulting in deregulation of the high mobility group A2 (HMGA2) gene; (2) deletion of material from the long arm of chromosome 13 (13q); (3) supernumerary ring chromosomes; and (4) rearrangement of chromosome band 6p21 Mandahl et al, 1988Mandahl et al, , 1994Sreekantaiah et al, 1991;Ashar et al, 1995;Schoenmakers et al, 1995;Fletcher et al, 1996;Willé n et al, 1998;Dahlé n et al, 2003a;Bassett et al, 2005). At least one of these aberrations, which usually are mutually exclusive, is present in the great majority of all reported lipomas (Mitelman Database of Chromosome Aberrations in Cancer, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…This is important because molecular distinct tumor subtypes represent different diseases that ideally would require different treatments. Most recently, particular subtypes of liposarcoma have been found to be associated with specific chromosomal translocations and specific cytogenetic abnormalities (21)(22)(23) and have been used to improve the accuracy of subtype classification when combined with morphology. However, cytogenetic analysis is labor intensive and remains difficult to uniformly apply to all samples because some subtypes do not grow well in short-term culture.…”
Section: Discussionmentioning
confidence: 99%
“…2 A number of studies have shown that there is a strong correlation between the presence of supernumerary ring or giant marker chromosomes, derived from chromosome 12q13-15 where MDM2, CDK4, SAS, HMGIC and other genes are located, and the morphological features of atypical lipomatous tumors and dedifferentiated liposarcomas. These genetic abnormalities, originally reported using cytogenetics, 3,4 and subsequently by reverse transcription polymerase chain reaction, [5][6][7] fluorescence in situ hybridization (FISH), [8][9][10] and later with antibodies to MDM2 and CDK4, 5,8 demonstrated that MDM2 amplification occurs consistently in atypical lipomatous tumor in which CDK4 is also frequently amplified. In contrast, other genes in the chromosomal region 12q13-15 are less commonly associated with copy number gain 11,12 and in a small number of cases CDK4 amplification has been reported in the absence of MDM2 copy number gain.…”
mentioning
confidence: 99%